Development Of Pencak Silat Learning Model Based On Game Modification To Improve Gross Motor Ability Of Elementary School Children Phase C In Malang City - Terate Syura, Yukta (Proceeding of International Joint Conference on UNESA, 2025)
This study uses a descriptive model that aims to develop an effective, safe, and interesting game-based pencak silat learning model to improve gross motor skills of elementary school children. The method used is a simplified Borg and Gall research and development (R&D) model. The subjects of the study involved fifth grade students from 3 elementary schools in Malang City. The product developed is a module with 11 types of games, namely Silat Arah Ajaib, Squid Game Pencak Silat, Elak Tangkap, Ikuti Gerakanku, Elak Estafet, Silat Ninja, Engklek Ceria, Silat Jump Rope, Guardian of the Secret Gate, Secret Code of Silat, and Tembak Menara. Product validation was carried out by 3 experts, material experts who gave a 100% assessment for clarity, accuracy, suitability, ease, and completeness, but only 75% for attractiveness, so it is recommended to increase the attractiveness of the material. Media experts gave a score of 83% for clarity, 100% for accuracy, ease, and attractiveness, 92% for suitability, and 88% for completeness, with a note that there needs to be improvement in the clarity and completeness of the media. Meanwhile, practitioner experts gave 100% for clarity, accuracy, suitability, ease, and completeness, and 88% for attractiveness, indicating that the module is very feasible to use with slight improvements in the attractiveness aspect. Material, media, and practitioner experts showed an average score above 83% in all aspects. Small and large group trials produced an average student response score above 97% for the indicators of clarity, suitability, accuracy, ease, and attractiveness. The results show that this model is valid and feasible to be applied in PJOK learning, and should be further applied in order to effectively improve students’ gross motor skills. In addition, this model introduces pencak silat in a fun, contextual way, and is full of character values such as sportsmanship, cooperation, and courage